An ingenious 3D-printed navigating template for accurate screw placement in lumbar spinal stenosis - Zhang, Yaoshen; Li, Kangpeng; Ma, Rui; Liu, Yuzeng; Zhang, Qiang; Hai, Yong (Frontiers in Surgery, 2025)
ObjectiveTo investigate the feasibility, accuracy, and safety of using a 3D-printed navigating template in transforaminal lumbar intervertebral fusion (TLIF) for treating lumbar spinal stenosis (LSS).MethodsA retrospective analysis was conducted on single-segment lumbar vertebrae treated with TILF at Beijing Ditan Hospital between May 2023 and May 2024. Clinical data were collected from patients diagnosed with LSS. Among them, 36 patients who underwent surgery using a 3D-printed navigating template were assigned to the template group, while another 36 patients with similar baseline characteristics were included in the control group. The following parameters were recorded: operative time, blood loss, frequency and duration of fluoroscopy, accuracy of screw placement, and incidence of complications related to spinal cord or nerve injuries.ResultsThe operation time and blood loss in the template group were significantly lower than those in the control group (P < 0.05). The fluoroscopy time and frequency on the template side were also significantly lower than those on the puncture side and in the control group (P < 0.05). Notably, there were no grade 2 screws observed in the template group, whereas 14 grade 2 screws were identified in the control group. Furthermore, the proportion of grade 0 screws on both sides in the template group was significantly higher compared to the control group (P < 0.05). However, no statistically significant difference was observed between the two sides within the template group (P > 0.05). Additionally, none of the patients experienced complications such as spinal cord or nerve injury.ConclusionThe application of 3D-printed navigating templates in the treatment of LSS using TLIF is feasible. Despite the need to account for potential inaccuracies caused by skin movement and changes in body position during surgery, this technique represents a novel and viable minimally invasive approach for screw placement.